A low-deformation high-strength ceramic core and preparation method thereof

By calcining high-alumina bauxite powder, electromelted mullite powder and alumina powder at high temperature, combined with the synergistic effect of toughening agents, low-deformation high-strength ceramic cores are prepared, which solves the problem of sintering deformation and insufficient strength of the ceramic core in high-temperature environments, and achieves a significant improvement in high-temperature performance and strength.

CN119114851BActive Publication Date: 2025-04-15SHENYANG RES INST OF FOUNDRY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411263527.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-04-15
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The existing ceramic cores have problems of sintering deformation and insufficient strength in high-temperature environments, making it difficult to meet the needs of high-performance aerospace engine components.

Method used

The precise ratio of high-temperature calcined high-alumina bauxite powder, electromelted mullite powder and alumina powder is used to prepare a low-deformation high-strength ceramic core with the synergistic effect of toughening agent, pore-forming agent and plasticizer.

Benefits of technology

The dimensional stability, high-temperature performance and strength of the ceramic core are significantly improved, and the high-temperature casting needs of hollow directional/single crystal castings and polycrystalline hollow castings are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114851B_ABST
    Figure CN119114851B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of investment casting of hollow castings, and specifically to a low-deformation high-strength ceramic core and a preparation method thereof, comprising a ceramic core powder, wherein the ceramic core powder comprises 30-85% of high-temperature calcined high-alumina bauxite powder, 10-50% of fused mullite powder and 1-20% of alumina powder by mass percentage. The present invention uses a precise ratio of high-temperature calcined high-alumina bauxite powder, fused mullite powder and alumina powder, combined with the synergistic effect of a toughening agent, a pore-forming agent and a plasticizer, to prepare a ceramic core having a lower deformation amount and a higher high-temperature strength, and can meet the needs of high-temperature cast hollow directional / single crystal castings and polycrystalline hollow castings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of investment casting of hollow castings, and in particular to a low-deformation and high-strength ceramic core and a preparation method thereof. Background Art

[0002] With the improvement of thrust-to-weight ratio of aerospace engines, the temperature of turbine front inlet continues to rise, the design structure of the inner cavity of hollow blade castings becomes more and more complex, and the performance requirements of ceramic cores are also increasing. The performance quality of ceramic cores directly affects the inner cavity dimensional accuracy, casting qualification rate and casting cost of hollow blades. Therefore, ceramic cores are required to have sufficient mechanical strength, good dimensional stability and excellent high temperature creep resistance. At present, the commonly used ceramic cores are mainly silicon-based ceramic cores and aluminum-based ceramic cores. Silicon-based ceramic cores have certain high temperature strength and are easy to remove. Aluminum-based ceramic cores have high high temperature bending strength, excellent chemical stability and excellent high temperature creep resistance.

[0003] The existing Chinese patent CN202110506145.9 discloses a large-sized silicon-based ceramic core and a preparation method thereof, wherein the raw material components of the large-sized silicon-based ceramic core include: ceramic powder, thermal conductor, pore former and plasticizer; the content of the thermal conductor is 0.5wt% to 5wt% of the mass of the ceramic powder, the content of the pore former accounts for 3wt% to 15wt% of the mass of the ceramic powder, and the content of the plasticizer accounts for 12wt% to 28wt% of the mass of the ceramic powder. Although the surface cracking problem is solved and the core removal time is shortened, the following disadvantages still exist: First, the method fails to effectively solve the deformation problem of the large-sized core, especially the dimensional stability under high temperature environment still needs to be improved; whether it is a silicon-based core or an aluminum-based core, there is a sintering deformation problem when hot pressing is used for molding, especially for some cores with narrow and long, large thin-to-thick transition and large chord-width ratio structure, the deformation problem becomes a key factor affecting the qualified rate. Secondly, although this method improves the core strength, the strength level of 12 MPa may still be insufficient for some high-performance aerospace engine components. Summary of the invention

[0004] In view of this, the present invention proposes a low-deformation and high-strength ceramic core and a preparation method thereof to solve the problem that the core prepared by the prior art has sintering deformation and insufficient core strength, which makes it difficult to meet the needs of high-temperature casting hollow directional / single crystal castings and polycrystalline hollow castings.

[0005] The technical solution of the present invention is achieved in this way:

[0006] In a first aspect, the present invention provides a low-deformation and high-strength ceramic core, comprising a ceramic core powder, wherein the ceramic core powder comprises, by mass percentage, 30-85% of high-temperature calcined high-alumina bauxite powder, 10-50% of fused mullite powder and 1-20% of alumina powder.

[0007] On the basis of the above technical scheme, preferably, the calcination temperature of the high-alumina bauxite powder calcined at high temperature is ≥1500°C, and the Al content of the high-alumina bauxite powder calcined at high temperature is 2 O 3 Content ≥85wt.%; melting temperature of fused mullite powder ≥1900℃; Al in fused mullite powder 2 O 3 The content is 93-97wt.%.

[0008] Specifically, in the present invention, high-alumina bauxite powder is calcined at high temperature (calcination temperature ≥ 1500°C, Al 2 O 3 Content ≥ 85wt.%) as the main matrix material, compared with the ordinary calcination temperature of about 1350℃ bauxite, calcination at 1500℃ high temperature makes the volume density of bauxite higher, the apparent porosity lower, the volume expansion smaller, and the crystal phase is stable and the glass phase content is less, which is more conducive to the dimensional stability of the ceramic core. 2 O 3 High-alumina powder with a content of ≥85% contains more mullite crystal phase and corundum phase, and has more stable high-temperature performance. This stable crystal phase structure reduces the risk of phase change at high temperatures and reduces the glass phase content, thereby greatly improving the dimensional stability and high-temperature performance of the ceramic core.

[0009] Fused mullite is produced by electric melting at a temperature greater than 1900°C. 2 O 3 The content is (95±2)%, its crystal phase is more stable, and it basically does not participate in liquid phase sintering, which is conducive to forming a stable size skeleton of the ceramic core.

[0010] High purity alumina powder (Al 2 O 3 Content ≥99.9%) is a fine powder with certain high temperature activity. As a mineralizer material, it promotes the solid phase sintering of bauxite and fused mullite, helps to form a dense microstructure at a lower temperature, and reduces the sintering temperature of the core.

[0011] On the basis of the above technical solution, preferably, the particle size of the high-temperature calcined high-alumina bauxite powder is 50-60 μm, the particle size of the fused mullite powder is 30-40 μm, and the particle size of the alumina powder is 6-15 μm.

[0012] The matrix is ​​prepared by mixing 30-85wt.% of high-alumina bauxite powder calcined at high temperature, 10-70wt.% of fused mullite powder, and 1-20wt.% of alumina powder, achieving the optimal balance of mullite, corundum and a small amount of glass phase, effectively inhibiting creep and deformation at high temperature; at the same time, the particle size distribution D50 of high-alumina bauxite calcined at high temperature is (50-60)μm, the D50 of fused mullite is (30-40)μm, and the Al2O3 powder is (10-20wt.%). 2 O 3 The particle size distribution is D50 (6-15) μm. The particle size distribution above is conducive to the formation of ceramic core powder particle size grading, and the combination of coarse and fine particles makes the core wet blank have higher compactness and lower porosity. This multi-level particle size design not only optimizes the packing density and improves the slurry fluidity, but also effectively controls the sintering shrinkage and reduces the risk of deformation. At the same time, a composite structure supported by a large particle skeleton, filled with medium particles, and lubricated with small particles is formed at the microscopic level, so that the coarse and fine particles are closely combined at the microscopic scale, which significantly improves the compactness of the core wet blank and reduces the porosity, thereby reducing the shrinkage space during the sintering process and effectively controlling the deformation.

[0013] On the basis of the above technical scheme, preferably, the ceramic core also includes a toughening agent, a pore former and a plasticizer, the toughening agent is added in an amount of 0.1-5% of the mass of the ceramic core powder; the pore former is added in an amount of 0.5-5% of the ceramic core powder, and the plasticizer is added in an amount of 17-20wt% of the ceramic core powder.

[0014] Specifically, the addition of toughening agent helps to improve the toughness of the ceramic core and reduce the risk of cracking; the use of pore-forming agent can form an appropriate pore structure during the sintering process, which is beneficial to the subsequent core removal process; and the plasticizer improves the fluidity and molding properties of the slurry.

[0015] On the basis of the above technical solution, preferably, the toughening agent is alumina fiber, the pore-forming agent is graphite powder, and the plasticizer is composed of 84-86wt.% paraffin wax, 8-12wt.% microcrystalline wax and 2-8wt.% beeswax.

[0016] On the basis of the above technical solution, preferably, the Al in the alumina fiber 2 O 3 The content is ≥95wt.%, the diameter of the alumina fiber is 3-5μm, and the length of the single fiber is 5-80mm; the C content of the graphite powder is ≥99wt.%, and the particle size of the graphite powder is 15-25μm.

[0017] Alumina fiber is used as a toughening agent. The fiber can form a good interface with the ceramic matrix at high temperature, absorb fracture energy through crack bridging, fiber pull-out and other mechanisms, significantly improve the thermal shock resistance and overall toughness of the ceramic core, and reduce the risk of cracking caused by thermal stress during use; graphite powder is used as a pore-forming agent. During the sintering process, the gradual oxidation of graphite powder can also provide additional sintering space for the surrounding ceramic particles, which helps to form a denser skeleton structure, while ensuring porosity without excessively reducing the strength of the material. Paraffin, microcrystalline wax and beeswax are compounded plasticizers. Paraffin is the main component, which provides good fluidity and formability, so that the ceramic slurry can evenly fill complex molds; the addition of microcrystalline wax increases the viscosity and plasticity of the mixture, and improves the strength and surface finish after molding; beeswax further optimizes the adhesion and plasticity of the mixture, and its natural emulsification properties help to improve the compatibility of ceramic powder and wax. The three compounding can not only fully fill the details of the mold, but also maintain sufficient strength to prevent deformation.

[0018] In a second aspect, the present invention provides a method for preparing a low-deformation and high-strength ceramic core, comprising the following steps:

[0019] S1, high temperature calcined high alumina bauxite powder, fused mullite powder and alumina powder are mixed into a matrix, toughening agent, pore former and plasticizer are added, and mixed evenly to obtain a slurry;

[0020] S2. Pressing the slurry into a wet blank, trimming and shaping the blank, and then firing the blank to obtain a ceramic core.

[0021] On the basis of the above technical solution, preferably, step S1 specifically includes:

[0022] S11, mixing high-temperature calcined high-alumina bauxite powder, fused mullite powder and alumina powder for 15-60 minutes to obtain a matrix, adding a toughening agent to the matrix, mixing for 5-10 minutes, and obtaining a fiber ceramic mixture;

[0023] S12, melt the plasticizer at 80-120°C, add the fiber ceramic mixture, mix well, then add the pore former, continue stirring for at least 48 hours to obtain a slurry.

[0024] Specifically, the addition of toughening agents can significantly improve the toughness and crack resistance of the ceramic core without excessively affecting other properties; the secondary mixing time of 5-10 minutes ensures the uniform distribution of the toughening agent in the matrix, forming a network structure that effectively prevents the expansion of cracks.

[0025] On the basis of the above technical solution, preferably, step S2 specifically includes:

[0026] The slurry is pressed into a wet blank at a pressure of 30-70 bar, and after trimming and shaping, it is sintered at a high temperature of 1320-1380°C for 6-12 hours and slowly cooled to obtain a ceramic core.

[0027] In a third aspect, the present invention provides an application of a low-deformation and high-strength ceramic core, wherein the low-deformation and high-strength ceramic core is used for the preparation of hollow directional / single crystal castings and polycrystalline hollow castings.

[0028] The low-deformation and high-strength ceramic core and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:

[0029] (1) Through the precise proportion of high-alumina bauxite powder, fused mullite powder and alumina powder calcined at high temperature, combined with the synergistic effect of toughening agent, pore former and plasticizer, the ceramic core has low deformation and high high-temperature strength, which can meet the needs of high-temperature casting hollow directional / single crystal castings and polycrystalline hollow castings;

[0030] (2) High-alumina bauxite powder calcined at high temperature provides a stable crystal structure and high-temperature strength, the stable crystals of fused mullite powder enhance thermal shock resistance and overall toughness, and high-purity alumina powder improves refractoriness and promotes solid-phase sintering, achieving an optimal balance among mullite, corundum and a small amount of glass phase. A multi-level particle size distribution design is adopted to form a composite structure with large particle skeleton support, medium particle filling and small particle lubrication, which significantly improves the compactness and dimensional stability of the core, effectively controls deformation and shrinkage at high temperature, and lays a solid material foundation for the low deformation and high strength characteristics of the ceramic core. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 The present invention is a flow chart for preparing a low-deformation and high-strength ceramic core. DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Unless otherwise specified, the raw materials used in the following examples and comparative examples are all commercially available.

[0035] High-alumina bauxite was purchased from Henan Bafang Water Purification Material Co., Ltd. High-temperature calcined high-alumina bauxite powder was obtained by calcining high-alumina bauxite at a temperature above 1500°C, with a particle size of 50-60 μm; fused mullite powder was purchased from Henan Dahua New Materials Co., Ltd., with a fusion temperature of ≥1900°C and a particle size of 325 mesh; alumina powder was purchased from Yumu (Ningbo) New Materials Co., Ltd., with the item number YM-Al 2 O 3 -W10, with a particle size of 10 μm; alumina fiber was purchased from Jinan Shengyu New Materials, with an average diameter of 3-4 μm and an alumina content of 95-97%; graphite powder was purchased from Shanghai Yuanye Biotechnology Co., Ltd., with a purity of 99%, a particle size of 750-800 mesh, and a CAS number of 7782-42-5.

[0036] Example 1

[0037] This embodiment provides a low-deformation high-strength ceramic core and a preparation method thereof, comprising the following steps:

[0038] S1. Pour 30kg of high-temperature calcined high-alumina bauxite powder, 22kg of fused mullite powder and 8kg of alumina powder into a mixer and mix for 15 minutes to obtain a matrix. Weigh 0.1kg of alumina fiber and add it to the matrix. Continue mixing for 5 minutes to obtain a fiber ceramic mixture. Weigh 9.18kg of paraffin wax, 1.08kg of microcrystalline wax and 0.54kg of beeswax to form a plasticizer. Add the plasticizer to a slurry mixer with a slurry barrel temperature of 95°C. After the plasticizer is completely melted, turn on the stirring and add the fiber ceramic mixture. After all the fiber ceramic mixture is added to the mixer, add 0.8kg of graphite powder and continue stirring for 48 hours to obtain a slurry.

[0039] S2. The obtained slurry is added to a high-pressure core pressing machine, and the slurry is pressed into a wet blank under a pressure of 50 bar. The wet blank is placed in a resistance furnace for baking after trimming and shaping. The core baking process is a final baking temperature of 1340°C and a heat preservation time of 8 hours. The baked core is cleaned and strengthened to obtain a finished ceramic core.

[0040] Example 2

[0041] This embodiment provides a low-deformation high-strength ceramic core and a preparation method thereof, comprising the following steps:

[0042] S1. Pour 45kg of high-temperature calcined high-alumina bauxite powder, 13kg of fused mullite powder and 5.4kg of alumina powder into a mixer and mix for 15 minutes to obtain a matrix. Weigh 0.08kg of alumina fiber and add it to the matrix. Continue mixing for 5 minutes to obtain a fiber ceramic mixture. Weigh 10.2kg of paraffin wax, 1.2kg of microcrystalline wax and 0.6kg of beeswax to form a plasticizer. Add the plasticizer to a slurry mixer with a slurry barrel temperature of 95°C. After the plasticizer is completely melted, turn on the stirring and add the fiber ceramic mixture. After all the fiber ceramic mixture is added to the mixer, add 1kg of graphite powder and continue stirring for 48 hours to obtain a slurry.

[0043] S2. The obtained slurry is added to a high-pressure core pressing machine, and the slurry is pressed into a wet blank under a pressure of 50 bar. The wet blank is placed in a resistance furnace for baking after trimming and shaping. The core baking process is a final baking temperature of 1360°C and a heat preservation time of 6 hours. The baked core is cleaned and strengthened to obtain a finished ceramic core.

[0044] Example 3

[0045] This embodiment provides a low-deformation high-strength ceramic core and a preparation method thereof, comprising the following steps:

[0046] S1. Pour 30kg of high-temperature calcined high-alumina bauxite powder, 50kg of fused mullite powder and 20kg of alumina powder into a mixer and mix for 35 minutes to obtain a matrix. Weigh 2.5kg of alumina fiber and add it to the matrix. Continue mixing for 8 minutes to obtain a fiber ceramic mixture. Weigh 14.28kg of paraffin wax, 1.36kg of microcrystalline wax and 1.36kg of beeswax to form a plasticizer. Add the plasticizer to a slurry mixer with a slurry barrel temperature of 80°C. After the plasticizer is completely melted, turn on the stirring and add the fiber ceramic mixture. After all the fiber ceramic mixture is added to the mixer, add 0.55kg of graphite powder and continue stirring for 52 hours to obtain a slurry.

[0047] S2. The obtained slurry is added to a high-pressure core pressing machine, and the slurry is pressed into a wet blank under a pressure of 30 bar. The wet blank is placed in a resistance furnace for baking after trimming and shaping. The core baking process is a final baking temperature of 1320°C and a heat preservation time of 12 hours. The baked core is cleaned and strengthened to obtain a finished ceramic core.

[0048] Example 4

[0049] This embodiment provides a low-deformation high-strength ceramic core and a preparation method thereof, comprising the following steps:

[0050] S1. Pour 85kg of high-temperature calcined high-alumina bauxite powder, 10kg of fused mullite powder and 5kg of alumina powder into a mixer and mix for 60 minutes to obtain a matrix. Weigh 5kg of alumina fiber and add it to the matrix. Continue mixing for 10 minutes to obtain a fiber ceramic mixture. Weigh 17.2kg of paraffin wax, 2.4kg of microcrystalline wax and 0.4kg of beeswax to form a plasticizer. Add the plasticizer to a slurry mixer with a slurry barrel temperature of 120°C. After the plasticizer is completely melted, turn on the stirring and add the fiber ceramic mixture. After all the fiber ceramic mixture is added to the mixer, add 5.5kg of graphite powder and continue stirring for 48 hours to obtain a slurry.

[0051] S2. The obtained slurry is added to a high-pressure core pressing machine, and the slurry is pressed into a wet blank at a pressure of 70 bar. The wet blank is placed in a resistance furnace for baking after trimming and shaping. The core baking process is a final baking temperature of 1380°C and a heat preservation time of 6 hours. The baked core is cleaned and strengthened to obtain a finished ceramic core.

[0052] Comparative Example 1

[0053] This comparative example provides a low-deformation high-strength ceramic core and a preparation method thereof, comprising the following steps:

[0054] S1. Pour 25kg of high-temperature calcined high-alumina bauxite powder, 53kg of fused mullite powder and 22kg of alumina powder into a mixer and mix for 15 minutes to obtain a matrix. Weigh 0.1kg of alumina fiber and add it to the matrix. Continue mixing for 5 minutes to obtain a fiber ceramic mixture. Weigh 9.18kg of paraffin wax, 1.08kg of microcrystalline wax and 0.54kg of beeswax to form a plasticizer. Add the plasticizer to a slurry mixer with a slurry barrel temperature of 95°C. After the plasticizer is completely melted, turn on the stirring and add the fiber ceramic mixture. After all the fiber ceramic mixture is added to the mixer, add 0.8kg of graphite powder and continue stirring for 48 hours to obtain a slurry.

[0055] S2. The obtained slurry is added to a high-pressure core pressing machine, and the slurry is pressed into a wet blank under a pressure of 50 bar. The wet blank is placed in a resistance furnace for baking after trimming and shaping. The core baking process is a final baking temperature of 1340°C and a heat preservation time of 8 hours. The baked core is cleaned and strengthened to obtain a finished ceramic core.

[0056] Comparative Example 2

[0057] This comparative example provides a low-deformation high-strength ceramic core and a preparation method thereof, comprising the following steps:

[0058] S1. Pour 30kg of calcined high-alumina bauxite powder (high-alumina bauxite was purchased from Henan Bafang Water Purification Materials Co., Ltd., with a calcination temperature of 1350°C and a particle size of 50-60μm), 22kg of fused mullite powder (purchased from Henan Dahua New Materials Co., Ltd., with a fusion temperature of less than 1900°C and a particle size of 325 mesh) and 8kg of alumina powder into a mixer and mix for 15 minutes to obtain a matrix, weigh 0.1kg of alumina fiber and add it to the matrix, continue mixing for 5 minutes to obtain a fiber ceramic mixture; weigh 9.18kg of paraffin wax, 1.08kg of microcrystalline wax and 0.54kg of beeswax to form a plasticizer, add the plasticizer to a slurry mixer with a slurry barrel temperature of 95°C, turn on stirring after the plasticizer is completely melted, add the fiber ceramic mixture, and after all the fiber ceramic mixture is added to the mixer, then add 0.8kg of graphite powder, continue stirring for 48 hours to obtain a slurry.

[0059] S2. The obtained slurry is added to a high-pressure core pressing machine, and the slurry is pressed into a wet blank under a pressure of 50 bar. The wet blank is placed in a resistance furnace for baking after trimming and shaping. The core baking process is a final baking temperature of 1340°C and a heat preservation time of 8 hours. The baked core is cleaned and strengthened to obtain a finished ceramic core.

[0060] Comparative Example 3

[0061] This comparative example provides a low-deformation high-strength ceramic core and a preparation method thereof, comprising the following steps:

[0062] S1. Pour 30kg of high-temperature calcined high-alumina bauxite powder (particle size of 40-45μm), 22kg of fused mullite powder (purchased from Henan Dahua New Materials Co., Ltd., with a particle size of 20-25μm) and 8kg of alumina powder (purchased from Yumu (Ningbo) New Materials Co., Ltd., with item number YM-AI203-W70 and a particle size of 70μm) into a mixer and mix for 15 minutes to obtain a matrix, weigh 0.1kg of alumina fiber and add it to the matrix, continue mixing for 5 minutes to obtain a fiber ceramic mixture; weigh 9.18kg of paraffin wax, 1.08kg of microcrystalline wax and 0.54kg of beeswax to form a plasticizer, add the plasticizer to a slurry mixer with a slurry barrel temperature of 95°C, turn on stirring after the plasticizer is completely melted, add the fiber ceramic mixture, and after all the fiber ceramic mixture is added to the mixer, then add 0.8kg of graphite powder, continue stirring for 48 hours to obtain a slurry.

[0063] S2. The obtained slurry is added to a high-pressure core pressing machine, and the slurry is pressed into a wet blank under a pressure of 50 bar. The wet blank is placed in a resistance furnace for baking after trimming and shaping. The core baking process is a final baking temperature of 1340°C and a heat preservation time of 8 hours. The baked core is cleaned and strengthened to obtain a finished ceramic core.

[0064] Performance Testing

[0065] The room temperature strength, high temperature strength and thermal deformation of the ceramic cores prepared in the examples and comparative examples were tested according to the standard HB5353. The test results are shown in Table 1.

[0066] Table 1

[0067]

[0068] It can be seen from Table 1 that the ceramic core prepared by the present invention has good warm strength, high temperature strength and low thermal deformation.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A low-deformation and high-strength ceramic core, comprising ceramic core powder, characterized in that: In terms of mass percentage, the ceramic core powder comprises 30-85% of high-temperature calcined high-alumina bauxite powder, 10-50% of fused mullite powder and 1-20% of alumina powder; the fusion temperature of the fused mullite powder is ≥1900°C, and the Al2O3 content in the high-temperature calcined high-alumina bauxite powder is ≥85 wt.%; The particle size of high-temperature calcined high-alumina bauxite powder is 50-60 μm, the particle size of fused mullite powder is 30-40 μm, and the particle size of alumina powder is 6-15 μm; The ceramic core further comprises a toughening agent, a pore-forming agent and a plasticizer. The toughening agent is added in an amount of 0.1-5% of the total mass of the ceramic core powder; the plasticizer is added in an amount of 17-20wt% of the total mass of the ceramic core powder.

2. A low deformation and high strength ceramic core as claimed in claim 1, characterized in that: The calcination temperature of high-temperature calcined high-alumina bauxite powder is ≥1500°C, the Al2O3 content in the high-temperature calcined high-alumina bauxite powder is ≥85 wt.%, and the Al2O3 content in the fused mullite powder is 93-97 wt.%.

3. A low deformation and high strength ceramic core as claimed in claim 1, characterized in that: The toughening agent is alumina fiber, the pore-forming agent is graphite powder, and the plasticizer is composed of 84-86 wt.% of paraffin wax, 8-12 wt.% of microcrystalline wax and 2-8 wt.% of beeswax.

4. A low deformation and high strength ceramic core as claimed in claim 3, characterized in that: The Al2O3 content in the alumina fiber is ≥95 wt.%, the diameter of the alumina fiber is 3-5 μm, and the length of the single fiber is 5-80 mm; the C content of the graphite powder is ≥99 wt.%, and the particle size of the graphite powder is 15-25 μm.

5. A method for preparing a low-deformation and high-strength ceramic core according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, high temperature calcined high alumina bauxite powder, fused mullite powder and alumina powder are mixed into a matrix, toughening agent, pore former and plasticizer are added, and mixed evenly to obtain a slurry; S2. Pressing the slurry into a wet blank, trimming and shaping it, and then firing it to obtain a ceramic core.

6. The method for preparing a low-deformation and high-strength ceramic core according to claim 5, characterized in that: Step S1 specifically includes: S11, mixing high-temperature calcined high-alumina bauxite powder, fused mullite powder and alumina powder for 15-60 min to obtain a matrix, adding a toughening agent to the matrix, mixing for 5-10 min to obtain a fiber ceramic mixture; S12, melt the plasticizer at 80-120°C, add the fiber ceramic mixture, mix well, then add the pore former, continue stirring for at least 48 hours to obtain a slurry.

7. The method for preparing a low-deformation and high-strength ceramic core according to claim 5, characterized in that: Step S2 specifically includes: The slurry is pressed into a wet blank at a pressure of 30-70 bar, and after trimming and shaping, it is sintered at a high temperature of 1320-1380°C for 6-12 hours and slowly cooled to obtain a ceramic core.

8. Application of a low-deformation and high-strength ceramic core according to any one of claims 1 to 4, characterized in that: The low-deformation and high-strength ceramic core is used for preparing hollow directional / single crystal castings and polycrystalline hollow castings.

Citation Information

Patent Citations

  • Large-size silicon-based ceramic core and preparation method thereof

    CN115322009A

  • Method for preparing aluminum oxide base ceramic core

    CN101077836A

  • Preparation method of inert ceramic shell for directional or single-crystal high-temperature alloy investment casting

    CN117139560A